FRANK LLOYD WRIGHT’S SAMARA, ACOUSTICAL SOLUTIONS OF THE 1950’S - PANUSZKA, R. J.; PANUSZKA, K. A. (Archives of Acoustics, 2006)
The problem of environmental noise pollution concerns many Americans whose homes are near highways and busy streets. A famous American Architect, Frank Lloyd Wright, designed houses that have been noted for their architectural splendor and alleged acoustical superiority over more traditional designs. Mr. Wright's acoustical knowledge was tested by taking acoustical measurements and comparisons of traffic noise transferred from the adjacent highway (U S State Route 231). The sample home was a Usonian home and two traditionally designed houses located adjacent to Mr. Wright's design. Noise levels were significantly lower in the Usonian home (called SAMARA by Mr. Wright) compared to the traditionally designed houses. A difference of about 10 dBA existed due to Mr. Wright's unique architectural design. Significant design concepts contributing to this reduction included the excavation depth of the house, screening by the carport, and screening by other natural screens like wintergreen trees and shrubs.